Antioxidative Effects of Curcumin on the Hepatotoxicity Induced by Ochratoxin A in Rats - Sara Damiano; Consiglia Longobardi; Emanuela Andretta; Francesco Prisco; Giuseppe Piegari; Caterina Squillacioti; Serena Montagnaro; Francesco Pagnini; Paola Badino; Salvatore Florio; Roberto Ciarcia (Antioxidants, 2021)
Ochratoxin A (OTA) is a powerful mycotoxin found in various foods and feedstuff, responsible for subchronic and chronic toxicity, such as nephrotoxicity, hepatotoxicity, teratogenicity, and immunotoxicity to both humans and several animal species. The severity of the liver damage caused depends on both dose and duration of exposure. Several studies have suggested that oxidative stress might contribute to increasing the hepatotoxicity of OTA, and several antioxidants, including curcumin (CURC), have been tested to counteract the toxic hepatic action of OTA in various classes of animals. Therefore, the present study was designed to evaluate the protective effect of CURC, a bioactive compound with different therapeutic properties on hepatic injuries caused by OTA in rat animal models. CURC effects were examined in Sprague Dawley rats treated with CURC (100 mg/kg), alone or in combination with OTA (0.5 mg/kg), by gavage daily for 14 days. At the end of the experiment, rats treated with OTA showed alterations in biochemical parameters and oxidative stress in the liver. CURC dosing significantly attenuated oxidative stress and lipid peroxidation versus the OTA group. Furthermore, liver histological tests showed that CURC reduced the multifocal lymphoplasmacellular hepatitis, the periportal fibrosis, and the necrosis observed in the OTA group. This study provides evidence that CURC can preserve OTA-induced oxidative damage in the liver of rats.